Impacto da dor na qualidade de vida em indivíduos com lesão medular - Bombardelli, Alessandra; Ferreira, Gisele Guedes (My University, 2021)
Objective: To analyze the impact of pain on the quality of life of individuals with spinal cord injury (SCI). Methods: A descriptive, associative study with a cross-sectional approach, in which 21 spinal cord injured patients, registered at the Clinical Center of the University of Caxias do Sul, participated. The EMADOR scale for pain assessment, the WHOQOL-bref for pain assessment was applied via video call, quality of life and a sample characterization questionnaire. Descriptive statistics, Pearson's Chi-square test and Eta² were used (p=0.05; values above 0.60 for associations). Results: The sample was predominantly male, with traumatic SCI over 36 months and with paraplegia. Most participants had chronic pain, in the trunk and abdomen, of reasonable intensity, punctual and described as uncomfortable. The assessment of quality of life indicated greater deficits in the physical and environmental domains. When associating the quality of life of patients with the level of pain (0 to 10), a weak association was observed. However, when associating the ategorization of quality of life with the level of pain, there was a significant association with the physical (0,05) and social (0,049) domains. Conclusion: It was observed that pain is frequent in these patients with SCI and that this can interfere with quality of life, especially considering the physical and social domains. [resumo fornecido pelos autores]
Objetivo: Analisar o impacto da dor na qualidade de vida de indivíduos com lesão medular (LM). Métodos: Estudo descritivo, de caráter associativo e abordagem transversal, onde participaram 21 pacientes lesados medulares, cadastrados no Centro Clínico da Universidade de Caxias do Sul. Foi aplicado via chamada de vídeo, a escala EMADOR para avaliação da dor, o WHOQOL-bref para avaliação de qualidade de vida e um questionário de caracterização amostral. Foi utilizada estatística descritiva, o Teste Qui-quadrado de Pearson e Eta² (p=0,05; valores acima de 0,60 para as associações). Resultados: Na amostra predominou o sexo masculino, com LM traumática superior a 36 meses e com paraplegia. A maioria dos participantes apresentavam dor crônica, na região de tronco e abdômen, de intensidade razoável, pontual e descrita como desconfortável. A avaliação da qualidade vida indicou maiores déficits nos domínios físicos e ambientais. Ao associar a qualidade de vida dos pacientes com o nível de dor (0 a 10), observou-se uma associação fraca. Entretanto, ao associar a categorização da qualidade de vida com o nível de dor, observou-se uma associação significativa com os domínios físico (0,05) e social (0,049). Conclusões: Observou-se que a dor é frequente nesses pacientes com LM e que isso pode interferir na qualidade de vida, principalmente considerando os domínios físico e social. [resumo fornecido pelos autores]
Keywords: Fisioterapia; Dor; Qualidade de vida; Medula espinhal